1963
DOI: 10.1097/00132586-196312000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethamivan (Vanillic Acid Diethylamide) on the Respiratory Response of Healthy Young Men to Carbon Dioxide in the Absence of Hypoxia

Abstract: The effect of ethamivan (vanillic acid diethylamide) on the ventilatory response to carbon dioxide has been investigated in healthy young adult males. Intravenous infusion of the drug at a rate of 9 mg/min causes respiratory stimulation depending in degree upon the prevailing alveolar CO2 tension. When the latter is low stimulation by the drug is most marked and may largely support respiration below the CO, threshold. As alveolar Pco2 increases, the effect of the drug disappears. These findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1963
1963
1964
1964

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Gas mixtures were supplied to the subjects, and ventilation and alveolar gas tensions measured, by methods and under conditions previously described [Cunningham et at., 1957;Anderton et al, 1962;. The subjects were all young, healthy volunteers, mostly male medical students; two nurses were the only females studied.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gas mixtures were supplied to the subjects, and ventilation and alveolar gas tensions measured, by methods and under conditions previously described [Cunningham et at., 1957;Anderton et al, 1962;. The subjects were all young, healthy volunteers, mostly male medical students; two nurses were the only females studied.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose we have used a modification, suggested by Mr. B. B. Lloyd, of the method we described previously [Anderton et al, 1962] [1958].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that during hyperventilation due to C02 there is good agreement between end-tidal PCO2 and arterial PCO2 if tidal volume is greater than 500 ml. in adults [Anderton et al, 1962]. When a steady state of V and alveolar pCO2 had been reached, the inspired C02 tension was increased to a level not exceeding 45 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Our present interest in this question arose from studies of C02-response before and during infusion of the analeptic drug ethamivan [Anderton et al, 1962]. By the conventional method, the construction of a C02-response line requires at least three steady-state determinations of ventilation and alveolar pCO2.…”
mentioning
confidence: 99%